2021
DOI: 10.3389/fmicb.2021.768724
|View full text |Cite
|
Sign up to set email alerts
|

New Data Define the Molecular Phylogeny and Taxonomy of Four Freshwater Suctorian Ciliates With Redefinition of Two Families Heliophryidae and Cyclophryidae (Ciliophora, Phyllopharyngea, Suctoria)

Abstract: Four suctorian ciliates, Cyclophrya magna Gönnert, 1935, Peridiscophrya florea (Kormos & Kormos, 1958) Dovgal, 2002, Heliophrya rotunda (Hentschel, 1916) Matthes, 1954 and Dendrosoma radians Ehrenberg, 1838, were collected from a freshwater lake in Ningbo, China. The morphological redescription and molecular phylogenetic analyses of these ciliates were investigated. Phylogenetic analyses inferred from SSU rDNA sequences show that all three suctorian orders, Endogenida, Evaginogenida, and Exogenida, are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…It is a speciose and cosmopolitan genus comprising nearly 40 nominal species found in various aquatic environments [ 23 , 24 , 25 , 26 , 37 , 38 ]. The living cell size, ciliature, and especially the structure of the oral apparatus are the most important criteria for species separation within the genus [ 4 , 20 ]. Based on the structure of M2a, Wang et al suggested that members of Pleuronema could be divided into two groups: ‘ coronatum -type’ with the posterior end of M2a hook-shaped, ‘ marinum -type’ characterized by the straight posterior end of M2a [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is a speciose and cosmopolitan genus comprising nearly 40 nominal species found in various aquatic environments [ 23 , 24 , 25 , 26 , 37 , 38 ]. The living cell size, ciliature, and especially the structure of the oral apparatus are the most important criteria for species separation within the genus [ 4 , 20 ]. Based on the structure of M2a, Wang et al suggested that members of Pleuronema could be divided into two groups: ‘ coronatum -type’ with the posterior end of M2a hook-shaped, ‘ marinum -type’ characterized by the straight posterior end of M2a [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The widely used staining modalities for tissue sections are hematoxylin-eosin (HE) staining, 15 Nissen (NI) staining, 16 and methyl green-pyronin (MGP) staining solution. 17 While there have been studies investigating the effects of staining methods on nucleic acid integrity, further investigation is needed, particularly regarding their effects on spatial transcriptomics. For example, it has been suggested that RNA damage may occur during the staining step prior to microdissection, resulting in the absence of gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Although only five valid species have been recognized so far, four of these need to be redescribed to reveal their living morphology, infraciliature, and molecular characters (Foissner et al, 1999(Foissner et al, , 2002. One of the most distinctive characters of Actinobolina species is their highly extensible and retractable tentacles throughout the cortex, functioning as prey-capturing organelles reminiscent of suctorians (Lynn, 2008;Ma et al, 2021). The genus Papillorhabdos has two species (type species P. multinucleata and P. carchesii) that do not have tentacles and are characterized by two notable characters: the absence of a circumoral kinety, supporting its assignment to the family Enchelyidae Ehrenberg, 1838; and a four-rowed dorsal brush, distinguishing it from other genera within this family.…”
Section: Introductionmentioning
confidence: 99%